INTERNATIONAL TRENDS IN THE DEVELOPMENT OF THE PRESCHOOL EDUCATION SYSTEM - Azizova Ziroat Baxodirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in this article, the best experiences of preschool education and education in foreign countries were studied on the basis of a comparative analysis. Information is provided about the forms and conditions of preschool education, mainly in developed Western and Eastern countries. As well as opinions on the content of reforms carried out in the field of preschool education and education in our country and its results are covered. Also, special attention is paid to the research carried out on the study of foreign experience in preschool education and education. Specific opinions are expressed about its methodological foundations. The role and importance of advanced experience in the education system in ensuring the development of states is revealed.